Pemikiran Ki Hadjar Dewantara dan Implikasinya Bagi Sekolah di Era Industri 5.0 - Fitri, Karina Rahmah; Kuswandi, Dedi; Wedi, Agus (Innovative: Journal Of Social Science Research, 2025)
This article aims to examine the thoughts of Ki Hadjar Dewantara through the Systematic Literature Review (SLR) approach and its implications in the development of education in the Industry 5.0 era. Ki Hadjar Dewantara, an Indonesian education figure who emphasizes the concept of "Education for Independence" and the principle of "Tri Pusat Pendidikan", provides a strong philosophical basis for Indonesian education that is oriented towards freedom, independence, and humanism. This study collects 10 scientific literatures from the last decade (2016–2024) that are relevant to the theme of education in the digital era and the principles of Dewantara education. This study finds that Dewantara education is still relevant and can be applied in the context of technology and innovation in the Industry 5.0 era, especially through the student-centered learning and project-based learning approaches.